EKSISTENSI TUHAN MENURUT SAID NURSI (STUDI TERHADAP KITAB RISALAH AL-NUR) - Alkan Junaidi (Manthiq, 2016)
Abstract: The Existence of God According to Said Nursi (Research on a Book of Risalah al-Nur). Philosophically, the existence of God Almighty require evidence which make its existence can be accepted by human. Here, Said Nursi did not interpret the phrase of unity literally, but he explained it clearly. Then the problem is examined in this study, first: how the views of Said Nursi About the Existence of God?, the second: how to prove the existence of God by Said Nursi in the Book of Risalah al-Nur? This type of research is library research, and methods used  in this research is qualitative descriptive. From this research it was discovered that God is a substance in perspective of Nursi Supreme Court which  will not be understood by the human mind. God is also the Supreme Substance plenary that his perfection can not be compared to anything. Nevertheless, for Nursi the grandeur and perfection of God is manifest in every face sheets of the universe,  both at the level of the macrocosm and microcosm, through the  properties, names, and  his deeds. For a proof of God’s existence, Nursi presents four arguments. First, the cosmological argument, that all the diversity in the universe, perfection is relative, the dependence of all creatures, and the uniqueness of each  creation, it shows  a present of Mandatory  Substance Almighty Creator  and the one who created of all things. Second, the ontological argument, it illustrates that good microcosm of the animate and inanimate, everything in nature voiced greatness and unity of God. Third, the teleological argument, the teleological universe,  there  is no order, relevance and harmonious cooperation between each  other with a specific purpose. God as the designer must be present as a source of harmony of the whole  of creation. Fourth, intuitive argument, the central argument of this is the conscience of every human being the most transparent proof of God’s existence.